Notes for a history of peruvian labor law - Motta Villegas, Juan Diego (2018)
In the present article, the author makes a brief recount in which the most significant events regarding what can be named as a “History of peruvian Labor Law” are told along the main periods of our history.In that way, this topic fathoms through periods such as the Inca Empire, the colony and the Republic appealing to the support of quotes from peruvian historians with the stature of Jorge Basadre and Julio Cotler. At the same time, the author establishes a direct and original correlation between the birth of the peruvian Labor Law and the origins of union liberty and trade union movements in Peru.